Application of Fractional Calculus in Engineering Sciences - Tenreiro Machado, J. A. (2008)
The Fractional Calculus (FC) goes back to the beginning of the theory of differential calculus. Nevertheless, the application of FC just emerged in the last two decades, due to the progress in the area of chaos and nonlinear dynamics that revealed subtle relationships with the FC concepts. In the field of dynamical systems theory some work has been carried out but the proposed models and algorithms are still in a preliminary stage of establishment. Having these ideas in mind, the paper discusses the application of FC in engineering sciences.